A comprehensive assessment of the transcriptome of cork oak (Quercus suber) through EST sequencing. (BMC genomics, 2014)
BACKGROUND: Cork oak (Quercus suber) is one of the rare trees with the ability to produce cork, a material widely used to make wine bottle stoppers, flooring and insulation materials, among many other uses. The molecular mechanisms of cork formation are still poorly understood, in great part due to the difficulty in studying a species with a long life-cycle and for which there is scarce molecular/genomic information. Cork oak forests are of great ecological importance and represent a major economic and social resource in Southern Europe and Northern Africa. However, global warming is threatening the cork oak forests by imposing thermal, hydric and many types of novel biotic stresses. Despite the economic and social value of the Q. suber species, few genomic resources have been developed, useful for biotechnological applications and improved forest management. RESULTS: We generated in excess of 7 million sequence reads, by pyrosequencing 21 normalized cDNA libraries derived from multiple Q. suber tissues and organs, developmental stages and physiological conditions. We deployed a stringent sequence processing and assembly pipeline that resulted in the identification of ~159,000 unigenes. These were annotated according to their similarity to known plant genes, to known Interpro domains, GO classes and E.C. numbers. The phylogenetic extent of this ESTs set was investigated, and we found that cork oak revealed a significant new gene space that is not covered by other model species or EST sequencing projects. The raw data, as well as the full annotated assembly, are now available to the community in a dedicated web portal at http://www.corkoakdb.org. CONCLUSIONS: This genomic resource represents the first trancriptome study in a cork producing species. It can be explored to develop new tools and approaches to understand stress responses and developmental processes in forest trees, as well as the molecular cascades underlying cork differentiation and disease response.
APS

Oak Root Response to Ectomycorrhizal Symbiosis Establishment: RNA-Seq Derived Transcript Identification and Expression Profiling (PLOS ONE, 2014)
Ectomycorrhizal symbiosis is essential for the life and health of trees in temperate and boreal forests where it plays a major role in nutrient cycling and in functioning of the forest ecosystem. Trees with ectomycorrhizal root tips are more tolerant to environmental stresses, such as drought, and biotic stresses such as root pathogens. Detailed information on these molecular processes is essential for the understanding of symbiotic tissue development in order to optimize the benefits of this natural phenomenon. Next generation sequencing tools allow the analysis of non model ectomycorrhizal plant-fungal interactions that can contribute to find the ``symbiosis toolkits'' and better define the role of each partner in the mutualistic interaction. By using 454 pyrosequencing we compared ectomycorrhizal cork oak roots with non-symbiotic roots. From the two cDNA libraries sequenced, over 2 million reads were obtained that generated 19552 cork oak root unique transcripts. A total of 2238 transcripts were found to be differentially expressed when ECM roots were compared with non-symbiotic roots. Identification of up-and down-regulated gens in ectomycorrhizal roots lead to a number of insights into the molecular mechanisms governing this important symbiosis. In cork oak roots, ectomycorrhizal colonization resulted in extensive cell wall remodelling, activation of the secretory pathway, alterations in flavonoid biosynthesis, and expression of genes involved in the recognition of fungal effectors. In addition, we identified genes with putative roles in symbiotic processes such as nutrient exchange with the fungal partner, lateral root formation or root hair decay. These findings provide a global overview of the transcriptome of an ectomycorrhizal host root, and constitute a foundation for future studies on the molecular events controlling this important symbiosis.
From Duplicate 2 (Oak Root Response to Ectomycorrhizal Symbiosis Establishment: RNA-Seq Derived Transcript Identification and Expression Profiling - Sebastiana, Monica; Vieira, Bruno; Lino-Neto, Teresa; Monteiro, Filipa; Figueiredo, Andreia; Sousa, Lisete; Pais, Maria Salome; Tavares, Rui; Paulo, Octaavio S)